Pengaruh Konsentrasi Polikaprolakton dan Kompatibiliser Asam Maleat Anhidrida Terhadap Karakteristik Komposit Bioplastik Maizena-Glukomanan - Hasibuan, Radja Zulfan; Harsojuwono, Bambang Admadi; Anggreni, Anak Agung Made Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 4 (2022): DesemberDO - 10.24843/JRMA.2022.v10.i04.p02, 2022)
The weaknesses of cornstarch and glucomannan bioplastic composites is they are hydrophilic, as a result, these bioplastic composites have swelling values, WVTR, tensile strength, elongation at break, and young modulus that not SNI. This study was to determine the effect of the concentration of polycaprolactone and maleic anhydride and their interaction on the characteristics of the cornstarch-glucomannan bioplastic composite, and to determine the concentration of polycaprolactone and maleic anhydride compatibilizer which can produce the best cornstrach-glucomannan bioplastic composite. This study used a randomized block design with two factors. The concentration of polycaprolactone which consists of 3 levels (10% ; 12.5% ; 15%). Factor II is the concentration of maleic anhydride which consists of 3 levels (2.5%; 5%; 7.5%). The variables observed were tensile strength, elongation at break, young modulus, swelling, WVTR, biodegradation and FTIR. The data obtained were analyzed for diversity (ANOVA) and continued with Duncan's test. The results showed that the concentration of polycaprolactone and maleic anhydride and their intereaction had a significant effect on tensile strength, young modulus, WVTR, and swelling except for the elongation at break and biodegradation. Concentration of 15% polycaprolactone and 5% maleic anhydride produced the best composite bioplastic with a tensile strength of 16.16 MPa, elongation at break of 2.610%, modulus young of 627 MPa, swelling of 30.26%, WVTR 0.64g/m2.hour and degradation time for 7.33 days. Cornstarch and glucomannan bioplastic composites with concentrations of polycaprolactone and maleic anhydride contain functional groups of expression -(CH2)n, alkane, hydroxyl alcohol, carboxyl, alkene, alkyne, alkanes, and carbonyl .